1993
DOI: 10.1128/aac.37.3.384
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antibacterial activities of T-3761, a new quinolone derivative

Abstract: T-3761, a new quinolone derivative, showed broad and potent antibacterial activity. Its MICs for 90% of the strains tested were 0.20 to 100 ,Lg/ml against gram-positive bacteria, including members of the genera Staphylococcus, Streptococcus, and Enterococcus; 0.025 to 3.13 ,ug/ml against gram-negative bacteria, including members of the family Enterobacteriaceae and the genus Haemophilus; 0.05 to 50 p,g/ml against glucose nonfermenters, including members of the genera Pseudomonas, Xanthomonas, Acinetobacter, Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 11 publications
(11 reference statements)
1
21
0
Order By: Relevance
“…Microscopically, both pathogens were seen to grow as a biofilm on the inside and the outside of the catheter, and it is likely that this mode of growth in some way impeded the effectiveness of the drug, although the exact mechanism behind this impedance was not identified. The therapeutic efficacy of ciprofloxacin against UTI including foreign body-associated UTI caused by several uropathogens has been shown previously (13,39,46). Our results are consistent with previous observations.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Microscopically, both pathogens were seen to grow as a biofilm on the inside and the outside of the catheter, and it is likely that this mode of growth in some way impeded the effectiveness of the drug, although the exact mechanism behind this impedance was not identified. The therapeutic efficacy of ciprofloxacin against UTI including foreign body-associated UTI caused by several uropathogens has been shown previously (13,39,46). Our results are consistent with previous observations.…”
Section: Discussionsupporting
confidence: 83%
“…Treatment of animals with catheter-associated infection commenced 2 days after bacterial challenge with a dose of 30 mg/kg of body weight ciprofloxacin given orally in 0.2 ml of water twice daily for four consecutive days. This dose of ciprofloxacin was previously shown to have bactericidal effect against several uropathogens in mouse models of experimental UTI (13,39,46). A second group of animals served as an untreated infection control group by being implanted with infected catheters and treated with saline.…”
Section: Methodsmentioning
confidence: 99%
“…Fukuoka et al reported the antibacterial activity of a new quinolone, T-3761 (13). This quinolone has a unique 1-aminocyclopropyl group at the C7 position (shown in Fig.…”
Section: Materuils and Methodsmentioning
confidence: 99%
“…This quinolone has a unique 1-aminocyclopropyl group at the C7 position (shown in Fig. 6), whose nature steers away from the traditional piperazine and pyrrolidine derivatives (13,29). The antibacterial activity of T-3761…”
Section: Materuils and Methodsmentioning
confidence: 99%
“…DU-6859a (DU) is a new fluoroquinolone antimicrobial agent with the chemical structure 7-[(7S)-7-amino-5-azaspiro [2,4]heptan-5-yl]-8-chloro-6-fluoro-1-[(lR,2S)-2-fluoro-1-cyclopropyl]-1,4-dihydro-4-oxo-3-quinolinecarboxylic acid sesquihydrate (25). Since the presently available fluoroquinolone agents possess only moderate activities against many gram-positive bacteria, recent efforts have been directed toward the synthesis of compounds which have greater activities against these organisms, such as tosufloxacin (1), sparfloxacin (1,3,9), CI-934 (4), WIN 57273 (7,15,17), PD 117596 (5), PD 127391 (CI-960) (5,9,20), PD 131628 (9), T-3761 (10), OPC-17116 (14), AM-1155 (13), E-4497 (11), CP-74667 (16), and CP-99219 (6). DU appears to be one of the most active of these agents (25).…”
mentioning
confidence: 99%